1997
DOI: 10.1164/ajrccm.156.1.9607030
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Routine Microbial Investigation in Ventilator-Associated Pneumonia

Abstract: The use of microbiologic investigations in routine clinical practice, their value in guiding antibiotic prescription, and their influence on outcome were prospectively studied in 113 consecutive adults who developed ventilator-associated pneumonia (VAP). Blood cultures were performed in 78.7% of cases, protected specimen brushing in 95.5%, and bronchoalveolar lavage in only 45.1%. No causative agent was identified in 13 episodes (11.5%), and results of microbial tests directed a change in therapy in 43 (38.0%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
260
5
15

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(288 citation statements)
references
References 14 publications
8
260
5
15
Order By: Relevance
“…The organisms associated with ventilator-associated pneumonia that we identified are similar to those reported in the literature. 12,13,15,16,18 The most common causes overall are P. aeruginosa and Staphylococcus aureus. Early cases of ventilator-associated pneumonia are more commonly associated with methicillin-sensitive Staphylococcus aureus and late cases with methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The organisms associated with ventilator-associated pneumonia that we identified are similar to those reported in the literature. 12,13,15,16,18 The most common causes overall are P. aeruginosa and Staphylococcus aureus. Early cases of ventilator-associated pneumonia are more commonly associated with methicillin-sensitive Staphylococcus aureus and late cases with methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate antibiotic therapy has been associated with increased mortality from ventilator-associated pneumonia in several studies. 7,[9][10][11][12][13][14] Risk factors for receiving inadequate antimicrobial therapy include prior antibiotic exposure, presence of invasive devices, prolonged hospital stay, and prolonged ventilatory support. 14 Several studies have recommended that antibiotic choices be guided by knowledge of the common etiologic agents for ventilator-associated pneumonia in individual hospitals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that an inadequate antibiotic treatment is related to a poor prognosis [3,13]. The isolation of the causative organism and the investigation of the susceptibility to antibiotics may allow a more appropriate and adjusted treatment with potential bene®ts for the patient as well as for the antibiotic policy of the hospital.…”
Section: Reasons To Perform Microbial Investigationmentioning
confidence: 99%
“…Além de dificuldades diagnósticas, a causa é outro desafio. Métodos quantitativos e qualitativos têm sido testados [4][5][6] . Entre vários métodos de cultura, a quantitativa por lavado broncoalveolar (LBA) é a mais utilizada.…”
unclassified